Thematic Culinary Tourism Routes in Medan City Based on the Preferences of Domestic Tourists - Awaliya, Latifah; Liyushiana; Darmawan, Rahmat (Gastronomy and Culinary Art, 2026)
This study aims to identify domestic tourists’ preferences toward culinary tourism in Medan City, design thematic culinary tourism routes, and evaluate the routes using the Technology Acceptance Model (TAM). The research employed a descriptive quantitative approach through questionnaires distributed to 68 respondents, supported by field observations and secondary digital data. The analysis examined culinary preferences, tourism attributes, generational consumption patterns, and digital route acceptance. The findings indicate that aesthetic or Instagrammable culinary experiences ranked highest (25%), followed by halal culinary (22.06%) and street food (20.59%). Visual appeal, religiosity, and affordability were identified as the main determinants of destination choice. The results also highlight strong digital-native behavior and social media influence among young tourists. Based on these findings, three thematic culinary routes were developed according to food categories, mealtime functions, and facility convenience. TAM evaluation produced a Perceived Usefulness score of 3.5 and a Perceived Ease of Use score of 3.7, indicating positive user acceptance. The study concludes that Google My Maps can effectively support innovative culinary tourism route planning while strengthening Medan City’s culinary identity.